Nasza niebajka – parafrazy tekstów reklamowych w „Dniu świra” Marka Koterskiego - Miławska, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2014)
In the movie Dzień świra – one of the most popular Polish comedies of the recent years – Marek Koterski presents his personal vision of the Polish language. The director, recognizing the advertising messages as an important phenomenon of the modern culture, makes a paraphrase of such texts – both in their verbal and visual layer. Conducting various linguistic experiments, he reveals manipulative mechanisms of advertising slogans. Parodies and caricatures are intended to demonstrate a fictional harmony of advertising texts – instead of the desired fabulous world, the spectator (and reader) is forced to receive brutal messages, going beyond the sphere of taboo.